IRAK2, an IL1R/TLR Immune Mediator, Enhances Radiosensitivity via Modulating Caspase 8/3-Mediated Apoptosis in Oral Squamous Cell Carcinoma - Yu, Chih-Chia; Chan, Michael W.Y.; Lin, Hon-Yi; Chiou, Wen-Yen; Lin, Ru-Inn; Chen, Chien-An; Lee, Moon-Sing; Chi, Chen-Lin; Chen, Liang-Cheng; Huang, Li-Wen; Chew, Chia-Hui; Hsu, Feng-Chun; et al. (Frontiers in Oncology, 2021)
Predicting and overcoming radioresistance are crucial in radiation oncology, including in managing oral squamous cell carcinoma (OSCC). First, we used RNA-sequence to compare expression profiles of parent OML1 and radioresistant OML1-R OSCC cells in order to select candidate genes responsible for radiation sensitivity. We identified IRAK2, a key immune mediator of the IL-1R/TLR signaling, as a potential target in investigating radiosensitivity. In four OSCC cell lines, we observed that intrinsically low IRAK2 expression demonstrated a radioresistant phenotype (i.e., OML1-R and SCC4), and vice versa (i.e., OML1 and SCC25). Next, we overexpressed IRAK2 in low IRAK2-expression OSCC cells and knocked it down in high IRAK2-expression cells to examine changes of irradiation response. After ionising radiation (IR) exposure, IRAK2 overexpression enhanced the radiosensitivity of radioresistant cells and synergistically suppressed OSCC cell growth both in vitro and in vivo, and vice versa. We found that IRAK2 overexpression restored and enhanced radiosensitivity by enhancing IR-induced cell killing via caspase-8/3-dependent apoptosis. OSCC patients with high IRAK2 expression had better post-irradiation local control than those with low expression (i.e., 87.4% vs. 60.0% at five years, P = 0.055), showing that IRAK2 expression was associated with post-radiation recurrence. Multivariate analysis confirmed high IRAK2 expression as an independent predictor for local control (HR, 0.11; 95% CI, 0.016 – 0.760; P = 0.025). In conclusion, IRAK2 enhances radiosensitivity, via modulating caspase 8/3-medicated apoptosis, potentially playing double roles as a predictive biomarker and a novel therapeutic target in OSCC.